Construction SMEs versus Economic Growth: The Eastern Cape Perspective - Lubabalo Flepisi; Anna Johanna Catharina Womack; Lawrence Mpele Lekhanya (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
Globally, small and medium enterprises (SMEs) are recognised as the engine and backbone of economic growth, especially for emerging countries such as South Africa. However, construction SMEs in South Africa are faced with some major challenges that hinder their contribution to the economic growth of the country. The study sought to investigate the factors that hinder the contribution of construction SMEs to the economic growth in the Eastern Cape province, in South Africa. The sample size of the study comprised 303 construction SME owners/managers in the Eastern Cape province. Nevertheless, for this conference, the findings of the study are based on the reviewed literature, supplemented by a pilot study with 30 construction SME owners/managers as participants. The study revealed key factors that influence the contribution of construction SMEs to economic growth in the Eastern Cape province. These factors include insufficient/inadequate financial resources, innovation, business management skills, and investment in human capital, as well as a lack of Information Technology use, along with skills shortages, and too many government regulations. The South African government and private sector thus need to develop mechanisms that will cushion construction SMEs through the development of policies that will enable these firms to contribute to economic growth.